Investigating antecedents and consequences of corporate communication management - Mohamad, Bahtiar (Universiti Utara Malaysia, 2009)
This paper analyses the influences of managerial communication, marketing communication and organizational communication on corporate communication. In addition, this paper shows how corporate communication management influences organizational performance. This research also investigates the role of corporate leadership in moderating the relationship between corporate communication and organizational performance. Three categories of antecedents, namely, management communication, marketing communication and organizational communication are gathered from the literature. Direct consequences and indirect consequences through relevant mediators are identified. Future research directions are also offered. The compendium of antecedents and consequences of Corporate Communication Management (CCM) can be used by corporate communication practitioners for their segmentation and target stakeholders.